EXPLORING IRAQI NURSES’ KNOWLEDGE TOWARD INFECTION CONTROL IN BURNING CENTER - Kadhim, Jihad Jawad (PT. Antis International Publisher, 2025)
Objective: The study aimed to assess knowledge level among nurses regarding infection control in burn units and to find out the relationship between nurses’ knowledge and their sociodemographic data. Method: A descriptive cross-sectional study was conducted from November 1st, 2023, until April 1st, 2024, involving a non-probability purposeful sample of 70 nurses working at the Burns Center in Najaf and Al-Sadr Teaching Hospital. Result: The findings indicated that the majority of nurses demonstrated a good knowledge level regarding infection control, with nurses’ educational level and the availability of protocols showing a statistically significant relationship with their knowledge. Novelty: This study highlights the critical role of nurses’ educational background and institutional support in shaping infection control practices in burn units, emphasizing the need for continuing education, larger-scale research across wider regions, and the use of mass media by the Ministry of Health to strengthen infection control knowledge among nursing staff.